EPSS – METHOD AND TOOLS FOR IMPROVING THE COMPETENCE IN THE XXI CENTURY - Gródek-Szostak, Zofia; Kajrunajtys, Danuta; Ocha Siguencia, Luis; Zaucha, Agnieszka Chęcińska (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The paper discusses the features and usability of Electronic Performance Support Systems (EPSS) in education and improving the competence of adults. It is a serious problem for enterprises to search for employees (definite period, employment of students) for work that requires the use of business software. Learning (training) in the performance of tasks in such environment is an investment (requires time and expense). EPSS have been designed as tools to reduce the number of hours of training involving a trainer (human). These systems are coached - supported by people who use business software in their work on an ongoing basis. In the research we present how to implement them and in which way their popularization can help in hiring people without special pre-preparation, and only with the basic computer skills.